IMPROVING NEWS WRITING SKILL THROUGH COOPERATIVE LEARNING JIGSAW TYPE FOR THE VIIID GRADE OF MTs PONDOK PESANTREN AS-SALAM - Mardiah Mardiah (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2014)
PENINGKATAN KETERAMPILAN MENULIS BERITA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS VIIID MTs PONDOK PESANTREN AS-SALAMAbstractBased on initial observations in the field, the student’s news writing skills MTs Boarding School As-Salam Naga Beralih Kampar regency was still low. This is caused by several factors, one of which is the selection of the learning modeling accuracies. Learning model used is still the main choice in lecture learning. Another factor that comes from the students was the lack of motivation to write the story because it was thought that writing a story is a difficult activity. To correct this condition carried through Classroom Action Research Type Jigsaw Cooperative Learning Model. The Purpose of this research class action (1) Describing the process of improving the student skill in writing news items in class VIII D of class VIIID MTs Boarding School As-Salam Naga Beralih Kampar regency increases trough Jigsaw cooperative learning model, and (2) describing the supporting factors improved writing skills class VIIID news MTs Boarding School As-Salam Naga Beralih Kampar regency increases trough Jigsaw cooperative learning model. Class room Action Research was conducted in two cycles. Each cycle through the stages of (1) planning, (2) actions, (3) observation, (4) reflection. The subjects were students of class VIIID Boarding School As-Salam Naga Switch Kampar regency. The results of this study showed an increase in news writing skills class VIIID with respect to completeness of the content of the news (5w +IH), regularity of exposure, use of effective sentences, vocabulary used, the accuracy of using EYD, and attractiveness of headlines along with the formulation of several contributing factors in improving writing news class VIIID boarding School As-Salam Naga Beralih Kampar regency. Jigsaw cooperative learning model type is suitable for use by teachersin teaching students to write news. Teachers should choose appropriate learning steps in using the model of cooperative learning Jigsaw type new sin the learning process.Keywords: Keterampilan, Menulis Berita, Model Pembelajaran Kooperatif, Tipe Jigsaw. AbstrakBerdasarkan pengamatan awal di lapangan, kemampuan menulis berita siswa Pesantren MTs As-Salam Naga Beralih Kabupaten Kampar masih rendah. Hal ini disebabkan oleh beberapa faktor, salah satunya adalah pemilihan ketepatan belajar modeling. Model pembelajaran yang digunakan masih menjadi pilihan utama dalam pembelajaran perkuliahan. Faktor lain yang datang dari para siswa adalah kurangnya motivasi untuk menulis cerita karena dianggap menulis sebuah cerita merupakan kegiatan yang sulit. Untuk memperbaiki kondisi ini dilakukan melalui Model Pembelajaran Kooperatif Tipe Pembelajaran Gergaji Kelas. Tujuan dari tindakan kelas penelitian ini (1) Mendeskripsikan proses peningkatan kemampuan siswa dalam menulis item berita di kelas VIII D Pondok Pesantren VIII As-Salam Naga Beralih meningkat melalui model pembelajaran kooperatif Jigsaw, dan (2) Menggambarkan faktor pendukung peningkatan kemampuan menulis kelas VIIID berita Pesantren MTs As-Salam Naga Beralih Kabupaten Kampar meningkat melalui model pembelajaran kooperatif Jigsaw. Ruang kelas Action Research dilakukan dalam dua siklus. Setiap siklus melalui tahapan (1) perencanaan, (2) tindakan, (3) observasi, (4) refleksi. Subyek penelitian adalah siswa kelas VIIID Pondok Pesantren As-Salam Naga Beralih Kabupaten Kampar. Hasil penelitian ini menunjukkan adanya peningkatan kemampuan menulis berita kelas VIIID sehubungan dengan kelengkapan isi berita (5w + IH), keteraturan keterpaparan, penggunaan kalimat efektif, kosakata yang digunakan, keakuratan penggunaan EYD, dan daya tarik. Berita utama beserta rumusan beberapa faktor pendukung dalam memperbaiki penulisan berita kelas VIIID pesantren As-Salam Naga Beralih Kabupaten Kampar. Jenis model pembelajaran kooperatif jigsaw sangat cocok untuk digunakan oleh guru dalam mengajar siswa menulis berita. Guru harus memilih langkah pembelajaran yang tepat dalam menggunakan model pembelajaran kooperatif tipe Jigsaw sin baru proses pembelajaran.Kata Kunci: Keterampilan, Menulis Berita, Model Pembelajaran Kooperatif, Tipe Jigsaw.